2023
DOI: 10.1021/acs.jpca.2c06908
|View full text |Cite
|
Sign up to set email alerts
|

Model Chemistry Recommendations for Scaled Harmonic Frequency Calculations: A Benchmark Study

Abstract: Despite the widespread popularity of scaled harmonic frequency calculations to predict experimental fundamental frequencies in chemistry, sparse benchmarking is available to guide users on the appropriate level of theory and basis set choices (model chemistry) or deep understanding of expected errors. An updated assessment of the best approach for scaling to minimize errors is also overdue. Here, we assess the performance of over 600 popular, contemporary, and robust model chemistries in the calculation of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…In the following this computational model is referred to simply as B3 and is used also for the computation of anharmonic contributions. The geometries and harmonic force fields of conformers lying within a predefined energy range are then refined by the revDSD-PBEP86-D3BJ/jun-cc-pv­(T+d)­Z model (hereafter rDSD), which provides excellent conformational landscapes, ,, geometries, dipole moments, and spectroscopic parameters. , In the present context, we will analyze in detail only conformers not involved in fast relaxation processes and with a relative free energy below 620 cm –1 at room temperature (i.e., a relative population of about 5% when only the considered conformer and the absolute free energy minimum are taken into account, since kT / hc = 207 cm –1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the following this computational model is referred to simply as B3 and is used also for the computation of anharmonic contributions. The geometries and harmonic force fields of conformers lying within a predefined energy range are then refined by the revDSD-PBEP86-D3BJ/jun-cc-pv­(T+d)­Z model (hereafter rDSD), which provides excellent conformational landscapes, ,, geometries, dipole moments, and spectroscopic parameters. , In the present context, we will analyze in detail only conformers not involved in fast relaxation processes and with a relative free energy below 620 cm –1 at room temperature (i.e., a relative population of about 5% when only the considered conformer and the absolute free energy minimum are taken into account, since kT / hc = 207 cm –1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that neglect of diffuse f functions on non-hydrogen atoms (which leads from the jul-cc-pVTZ to the jun-cc-pvTZ basis set) reduces the computational cost without any significant accuracy loss for geometries, 32 dipole moments, 51 and spectroscopic parameters. 39,52 The typical error of rDSD/j3 bond lengths and valence angles (0.3%) 32 is sufficient to obtain accurate relative electronic energies and vibrational spectra of different tautomers, but the situation is different for the leading terms of MW spectra, namely rotational constants of the vibrational ground-state (B i 0 , where i refers to the inertial axes a, b, c). These parameters include vibrational corrections (ΔB i vib ) in addition to equilibrium rotational constants (B i eq ).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Next, the geometries and harmonic force fields of the most stable species have been refined at the revDSD-PBEP86-D3BJ/jun-cc-pvTZ level (hereafter rDSD/j3). Several studies have shown that neglect of diffuse f functions on non-hydrogen atoms (which leads from the jul-cc-pVTZ to the jun-cc-pvTZ basis set) reduces the computational cost without any significant accuracy loss for geometries, dipole moments, and spectroscopic parameters. , …”
Section: Computational Detailsmentioning
confidence: 99%
“…To evaluate the accuracy of the fitted scaling factors, we calculated the median errors as a more robust evaluation compared to RMSE, which can be significantly influenced by outliers (Zapata Trujillo & McKemmish 2022, Zapata Trujillo & McKemmish 2023. Specifically, median errors refer to the median of the differences between the and .…”
Section: Methodsmentioning
confidence: 99%
“…The prediction can either base on harmonic approximation, or use the more accurate but also more expensive anharmonic method. To achieve a reliable prediction using the much cheaper harmonic calculations, scaling factors have been developed for correcting the computed frequencies (Pople et al 1993, Scott & Radom 1996, Zapata Trujillo & McKemmish 2023.…”
Section: Introductionmentioning
confidence: 99%